Prosodia de los enunciados interrogativos neutros y orientados en el español de la Ciudad de México - Mendoza, Erika (Borealis – An International Journal of Hispanic Linguistics, 2023)
The aim of this paper is to describe the prosodic features –nuclear pitch configurations and pitch range– of neutral and oriented interrogative utterances in the Spanish of Mexico City. We carried out a study of polar and wh- questions recorded in the free conversation module of the Corpus Norma Lingüística Culta (Lope Blanch 1971) and Habla Popular de la Ciudad de México (Lope Blanch 1976). The findings of the qualitative analysis show: i) the nuclear pitch configuration L* H% –with the variants L* LH%, L* ¡H%, !H* ¡H%– in information-seeking yes-no questions and confirmation questions, ii) the nuclear configuration L* L% documented in neutral wh- questions, and the boundary tone H% produced in the non-neutral condition –hypothetical or confirmative– of the utterance; iii) the use of the pitch range as a potential prosodic resource for the expression of lesser or greater knowledge about the expected answer. The spontaneous speech data partially confirm the descriptions based on discourse completion tasks for this variety of Spanish (de-la-Mota et al. 2010).